Contextual and Psychological Predictors of Militant Extremist Mindset in Youth - Vukčević Marković, Maša; Nicović, Aleksandra; Živanović, Marko (Frontiers in Psychology, 2021)
The present study aims to identify contextual and psychological factors of proneness to radicalization and violent extremism (RVE) operationalized through the Militant Extremist Mindset scale (MEM) consisting of three distinct aspects: Proviolence (PV), Vile World beliefs (VW), and trust in Divine Power (DP). A community sample of 271 high school students (72% females) from Belgrade and Sandžak regions in Serbia completed: 1) a 24-item MEM scale; 2) contextual measures including a 6-item scale of family dysfunction (FDys) and a 4-item composite measure capturing exposure to a harsh school environment and peer abuse (HSE); 3) psychological measures including the 9-item Right-Wing Authoritarianism scale (RWA), the 5-item Social Dominance Orientation scale (SDO), and the 20-item UCLA Loneliness scale (LON). A path analysis was conducted with contextual factors on the first and psychological factors on the second level of the model predicting the three factors of MEM. LON was positively predicted by FDys and HSE, SDO by HSE only, while RWA was positively predicted by FDys only. Contextual and psychological factors accounted for 27% of the variance in PV (LON, SDO), 15% of the variance in VW (FDys, SDO), and 31% of the variance in DP (RWA). Obtained findings reveal a complex interplay of contextual and psychological drivers in the prediction of different aspects of RVE and build upon existing knowledge on risk factors associated with RVE.